2021
DOI: 10.1021/acs.joc.1c02311
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Oxidative Amination of Benzylic C(sp3)–H Bonds with Anilines

Abstract: Iron-catalyzed oxidative amination of benzylic C-(sp 3 )−H bonds with anilines bearing electron-withdrawing groups (EWGs) or electron-donating groups (EDGs) is realized based on simple variations of N-substituents on imidazolium cations in novel ionic Fe(III) complexes. The structural modification of the imidazolium cation resulted in regulation of the redox potential and the catalytic performance of the iron metal center. Using DTBP as oxidant, [HItBu][FeBr 4 ] showed the highest catalytic activity for anili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Then, the reaction of C­(sp 3 ) radical A with the in situ formed Fe III –nitrogen complex B from the Fe III –Cl complex and N–H 1 provided the desired product 3 and the Fe II –Cl complex . Oxidation of the Fe II –Cl complex by DTBP or the tert -butoxyl radical regenerated the Fe III –Cl complex …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the reaction of C­(sp 3 ) radical A with the in situ formed Fe III –nitrogen complex B from the Fe III –Cl complex and N–H 1 provided the desired product 3 and the Fe II –Cl complex . Oxidation of the Fe II –Cl complex by DTBP or the tert -butoxyl radical regenerated the Fe III –Cl complex …”
Section: Resultsmentioning
confidence: 99%
“…13 Oxidation of the Fe II −Cl complex by DTBP or the tert-butoxyl radical regenerated the Fe III −Cl complex. 14…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In 2021, Hong-mei Sun and their colleagues synthesized various benzylic amines 160 from various aromatic amines 157 and toluene derivatives 158 using complex-159-A or complex-159-B (Scheme 40). [63] Optimization studies revealed that the 10 mol % [HSI t Bu][FeBr 4 ] (complex-159-A) or [HIPym][FeBr 4 ] (complex-159-B) as a catalyst and 1.5 equiv. DTBP as an oxidant at 120 °C for 24 h furnished the desired product in good yield.…”
Section: Iron Catalyzed Intermolecular C(sp 3 )à H Amination Reactionsmentioning
confidence: 99%
“…On the basis of the experimental results and a literature survey, a possible reaction pathway is described (Scheme a). On the anode, the benzylic C–H bond of ethylbenzene was oxidized by the −1e – /–1H + process, generating benzylic radical 1b-2 .…”
mentioning
confidence: 99%
“…Due to the relatively stable nature of the benzylic C–H bond, finding an efficient method to activate it has been an attractive challenge . The oxidative activation strategy is a commonly used method for benzylic C–H bond activation, where oxidants are applied to promote the formation of benzyl radicals and then attacked by nucleophilic reagents to generate products. Meanwhile, direct benzylic C–H bond amination, which transforms the C–H bond into the valuable C–N bond, can greatly accelerate the construction of complex molecules. , For example, Dauban and co-workers reported a method of intermolecular benzylic C–H bond amination by combining the pentafluorobenzyl sulfamate with a rhodium­(II) catalyst in the presence of an iodine­(III) oxidant (Scheme a) …”
mentioning
confidence: 99%